The comes sacrarum largitionum in the bureaucratic system of late antiquity - Pergami, Federico (Social Science Research Network, 2021)
The essay deals with the events of the introduction, in late antiquity’s burocratic order, of the comes sacrarum largitionum and studies its functions, especially in the second half of the fourth century, in relation to the activitity of another important officer, the comes rerum privatarum. The imperial constitutions allow us to hypothesize that between the two imperial financial departments there was no rigid separation of competences: it seems naturalthat, both were informed, from time to time, of measures concerning the one or the other branch of public property management.
Keywords: Comes rerum privatarum; Comes sacrarum largitionum; Imperial burocratic order; Imperial financial departments